Entre mata e gerais: produção de alimentos e autoconsumo por agricultores familiares da região do Alto-Médio São Francisco - MG - Alice Assis Carvalho (2011)
Family farmers are recognized as the mainly supplier of food that supply the national markets, but in addition to producing food they are also consumers. The objective of this dissertation is to analyze the production of food for selfconsumption by farmers in three rural communities of the Upper-Middle São Francisco: Ribeirão de Areia, Coqueiros and Barra do Tamboril. These communities were chosen because they keep the proper characteristics of environments of forest and gerais specific to the region of study and because they are inserted in the semiarid mineiro. The methodology used for data collection combined five research techniques: census survey, individual interviews, multicase study, ethnography and life history. It was observed that family farmers develop productive strategies through joint agricultural labor, migration, retirement and transfer of income to maintain the balance among consumption, number of family members and land. The mapping of the families feed showed to be the self-consumption in the symbolic and practicalplan the establishment of a productive and feed agenda extremely rich and diverse base of the food sovereignty of families.